1980
DOI: 10.1080/09553008014551341
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Radiobiological Oxygen Constant,K, and the Non-protein Sulphydryl Content of Mammalian Cells

Abstract: The value of the radiobiological oxygen constant K has been found to depend on the concentration of non-protein sulphydryl (NPSH) within the cell. Cells in the exponential phase of growth have a higher concentration of NPSH and a higher value of K than cells in plateau phase. Binding NPSH with N-ethylmaleimide reduced the value of K and conversely, addition of NPSH as dithioerythritol increased the value of K. K also rises with the same time course as NPSH increases, when plateau phase cells are replated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

1981
1981
1989
1989

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 14 publications
0
5
2
Order By: Relevance
“…Recent studies, using epidermal clones in vivo, have shown that the oxygen dependence of sulphydryl radioprotection is complex and depends on the precise oxygenation status, rather than simply on whether the cells are euoxic or hypoxic (Denekamp et al, 1981;. This agrees with in vitro studies with other sulphydryls, in bacteria and mammalian cells (Dewey, 1963;Cullen et al, 1980). Our data contrast with the report by Yuhas et al, (1977), who observed no reduction of radiosensitization in the line 1 carcinoma when WR-2721 was used in combination with MISO.…”
Section: Irradiationcontrasting
confidence: 57%
“…Recent studies, using epidermal clones in vivo, have shown that the oxygen dependence of sulphydryl radioprotection is complex and depends on the precise oxygenation status, rather than simply on whether the cells are euoxic or hypoxic (Denekamp et al, 1981;. This agrees with in vitro studies with other sulphydryls, in bacteria and mammalian cells (Dewey, 1963;Cullen et al, 1980). Our data contrast with the report by Yuhas et al, (1977), who observed no reduction of radiosensitization in the line 1 carcinoma when WR-2721 was used in combination with MISO.…”
Section: Irradiationcontrasting
confidence: 57%
“…The maximum radioprotection is seen just above the transition region from fully sensitive to fully resistant; this might be expected if the oxygen supply is then barely adequate and the sulphydryls and oxygen are competing for fixation and repair of damage. The in vitro data from Cullen et al (1980) showed a displacement of the oxygen K. curves when the sulphydryl dithioerythritol was added, but it occurred at a 40-fold lower oxygen concentration in the bubbled gas than in the inspired gas in vivo. Of course the ".Kinsp" value gives no direct information about the local oxygen tension at the critical site within the epidermal cells, so these data cannot be directly related to the /lvalues in vitro.…”
Section: (Authors' Reply)mentioning
confidence: 97%
“…Harris 1979;Cullen et al, 1980). Oxygen removal (by thiol oxidation) may be a common radioprotective mechanism.…”
Section: Discussionmentioning
confidence: 99%